Homestead laws - Bastable, C. F. (Statistical and Social Inquiry Society of Ireland, 1888)
The present paper aims at giving a concise account of the origin and development of the Homestead Laws of the United States, with notices of similar legislation to be found elsewhere. It next considers the practical working of the laws, and the various theories by which they are supported; and it finally endeavours to form some judgment as to the expediency of adopting the policy which is recommended to our attention.
Read Tuesday, 22nd November, 1887
Keywords: Homestead law; Land ownership; USA; 314.15